Clinical, histopathological and surgical evaluations of persistent oropharyngeal membrane case in a calf - Gunes, Vehbi; Atalan, Gultekin; Bayram, Latife Cakir; Varol, Kemal; Erol, Hanifi; Keles, Ihsan; Onmaz, Ali C (Archives of Case Reports, 2019)
A male, 4 days old and 20 kg Simmental calf was evaluated for regurgitation and hyper salivation since birth. The mother became pregnant by artificial insemination and the pregnancy was the second of the mother. A membrane closed the pharynx and a diverticulum on dorsal of this membrane was seen during oropharyngeal examination through inspection. Membrane was also viewed by endoscopy under general anaesthesia. Larynx and oesophagus were imaged by bronchoscopy through the back side of the membrane. After these applications, it was decided that soft palate adhered firmly to the root of tongue causing congenital atresia. Surgical treatment of oropharyngeal membrane was carried out under general anaesthesia. Firstly, tracheotomy was performed for to ease breathing and membrane removed by electrocautery application. Intensive fluid accumulation and oedema formation at the incision area were detected by endoscopic examination following operation and the calf had severe dyspnoea two days after operation and died due to respiratory insufficiency. At necropsy, severe inflammatory reaction, laryngeal oedema and intensive salivation at the surgical side was determined. Direct imaging techniques should be used to determine in the closed oropharyngeal lumen. Moreover, nasopharyngoscopy should be considered to image larynx and oesophageal way. Present case is the first report with concern to pharyngeal membrane formation together with direct imaging and surgical procedures. Therefore, it was considered that this case report could be useful for colleagues and literatures.